2005
DOI: 10.1182/blood-2004-06-2411
|View full text |Cite
|
Sign up to set email alerts
|

Donor CD8+ T cells facilitate induction of chimerism and tolerance without GVHD in autoimmune NOD mice conditioned with anti-CD3 mAb

Abstract: IntroductionType 1 diabetes is an autoimmune disease characterized by destruction of insulin-secreting pancreatic islet ␤ cells by pathogenic autoreactive T cells. 1,2 By most accounts, the nonobese diabetic (NOD) mouse represents an ideal animal model for human type 1 diabetes. 3 Female NOD mice develop insulitis at about 4 weeks of age and begin to show diabetes from about 15 weeks of age. 3 Induction of mixed chimerism via transplantation of bone marrow (BM) cells from nonautoimmune donors into autoimmune N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
58
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 65 publications
(87 reference statements)
1
58
1
Order By: Relevance
“…In addition, the HCT procedures used in those reports require total body irradiation conditioning of the recipients, and the toxicity of radiation and potential for graft-versushost disease (GVHD) limits its application in treating type 1 diabetic patients. We recently reported that transplantation of allogeneic donor BM and CD8 ϩ T cells into prediabetic NOD mice conditioned with anti-CD3 mAb induced chimerism without causing GVHD (27). In the current study, we showed that injection of donor BM and CD4 ϩ T cell-depleted spleen (SPL) cells induced chimerism in diabetic NOD mice conditioned with anti-CD3 and anti-CD8 mAb (anti-CD3/CD8).…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…In addition, the HCT procedures used in those reports require total body irradiation conditioning of the recipients, and the toxicity of radiation and potential for graft-versushost disease (GVHD) limits its application in treating type 1 diabetic patients. We recently reported that transplantation of allogeneic donor BM and CD8 ϩ T cells into prediabetic NOD mice conditioned with anti-CD3 mAb induced chimerism without causing GVHD (27). In the current study, we showed that injection of donor BM and CD4 ϩ T cell-depleted spleen (SPL) cells induced chimerism in diabetic NOD mice conditioned with anti-CD3 and anti-CD8 mAb (anti-CD3/CD8).…”
mentioning
confidence: 55%
“…This radiation-free regimen provides for induction of chimerism without GVHD in overtly diabetic NOD mice, and we demonstrate that this chimerism augments the regeneration of host islet ␤ cells. two injections of 20 ϫ 10 6 donor CD8 ϩ T cells (27). However, we also observed that the same dose of donor BM and CD8 ϩ T cells did not induce chimerism in diabetic NOD mice, whose blood glucose had been controlled with implantation of insulin pellets (data not shown).…”
mentioning
confidence: 60%
See 3 more Smart Citations